Achieving net-zero greenhouse gases will take civil engineers into uncharted territory. Issue 3 (June 2019) - Guthrie, Greg
Abstract : The UK Committee on Climate Change wants to achieve net-zero greenhouse gas emissions within the next 30 years. Greg Guthrie of the Institution of Civil Engineers' maritime panel says meeting the target will have profound implications for civil engineers.